IFPRI monthly maize market report, September 2019 - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Fluctuations in the price of maize—Malawi’s most important staple crop—are a huge contributor to the country’s overall food security. Providing maize price information in markets throughout the country is a critical first step to understanding and improving food security in Malawi. The Monthly Maize Market Report was developed by researchers at IFPRI Malawi with the goal of providing clear and accurate information on the variation of daily maize prices in selected markets throughout Malawi. The reports are intended as a resource for those interested in maize markets in Malawi, namely producers, sellers, consumers, or other agricultural stakeholders.